Innovative agroecological practices can restore degraded farmlands and revive crop yields - Ntamwira, Jules Bagula; Ocimati, Walter; Blomme, Guy; Lubobo, Antoine Kanyenga; Mwarabu Lolonga Pyame, Dieudonne; Dhed’a Djailo, Benoit (Frontiers Media, 2023)
Land degradation is a major obstacle to agricultural development in Africa, where it's accentuated by poor agricultural practices and climate change effects. Restoration of degraded lands is crucial to prevent incursions into virgin and marginal lands. A field experiment was carried out over a four-year period on two degraded sites, to assess and compare the effect of the common practices of: (i) burning crop residues and weeds by resource-poor farmers (T1) and (ii) burning crop residues and weeds followed with application of manure and/or NPK as external inputs (T2) by resource-endowed farmers with (iii) an innovative agroecological package (T3) on soil physical, chemical and biological attributes, and crop yields. T3 consisted of crop rotation and/ intercropping with Mucuna pruriens cover crop, grasses (Pennisetum purpureum and Setaria sphacelate) and shrubs (Calliandra calothyrsus, and Leucaena diversifolia), and the application of manure and NPK. A randomized complete block design with 8 and 10 blocks, with each package appearing once in each block, was used respectively, at Mulungu and Mushinga. The agroecological package significantly improved soil and plant parameters compared to the common practices at both sites. The average plot-level aboveground biomass was significantly lower (p < 0.001) in T1 (11.3–17.4 t/ha) and T2 (10.1–21.9) than in T3 (39.9–60.4 t/ha). Similar trends were observed for bean and maize grain and banana bunch yields. When T1 is compared to T3, mean yields increased 2.6 times (848 kg/ha against 327 kg/ha), 2.8 times (2,201 kg/ha against 792 kg/ha) and 1.5 times (7.4 t/ha against 5.0 t/ha) for bean grains, maize grain, and banana bunches, respectively. Improvements were also observed for soil physical, biological, and chemical properties. A decrease in soil temperature; and increases in soil porosity, earthworm density/m2 (1,932 against 0), nodules/bean plant (28 against 21) and root length density (65 against 15.5 cm) were observed in T3. T3 (compared to T1), had a decrease in acidity and Al3+; an increase in soil organic matter, K+, Ca+, and aboveground carbon stock (26.5 t/ha against 5.6 t/ha). The innovative agroecological package is thus an approach that can be used to effectively restore degraded and abandoned farmlands.